2018
DOI: 10.1021/jacs.8b00821
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Ring Contraction of Bromocycloheptenes through Dyotropic Rearrangements via Nonclassical Carbocation–Anion Pairs

Abstract: Experimental and theoretical evidence is reported for a rare type I dyotropic rearrangement involving a [1,2]-alkene shift, leading to the regio- and stereospecific ring contraction of bromocycloheptenes. This reaction occurs under mild conditions, with or without a Lewis acid catalyst. DFT calculations show that the reaction proceeds through a nonclassical carbocation–anion pair, which is crucial for the low activation barrier and enantiospecificity. The chiral cyclopropylcarbinyl cation may be a transition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…In the large asymmetric unit of the 1 ⋅ 2 structure, eight independent guest molecules were observed at sites A to H (Figure 2). [25] Seven of them at sites A to G showed R , R configuration. Interestingly, S , S configuration was observed for the guest trapped at the site H .…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…In the large asymmetric unit of the 1 ⋅ 2 structure, eight independent guest molecules were observed at sites A to H (Figure 2). [25] Seven of them at sites A to G showed R , R configuration. Interestingly, S , S configuration was observed for the guest trapped at the site H .…”
Section: Figurementioning
confidence: 97%
“…The CS method was applied to chiral homoallylic bromide 2 , which was synthesized in 88 % ee in the asymmetric synthesis study by the Feringa group [25] . After guest‐soaking experiment, the space group ( C 2/ c ) turned into non‐centrosymmetric C 2 and the crystal structure of guest‐absorbed 1 ⋅ 2 was solved in this space group.…”
Section: Figurementioning
confidence: 99%
“…In the large asymmetric unit of the 1•2 structure, eight independent guest molecules were observed at sites A to H (Figure 2). [25] Seven of them at sites A to G showed R,R configuration. Interestingly, S,S configuration was observed for the guest trapped at the site H. All the guests show normal pyramidalization angles at the sp 3 stereogenic centers, indicating that the disorder of S,S and R,R enantiomers at every site is negligible.…”
mentioning
confidence: 97%
“…The CS method was applied to chiral homoallylic bromide 2, which was synthesized in 88 % ee in the asymmetric synthesis study by the Feringa group. [25] After guest-soaking experiment, the space group (C2/c) turned into non-centrosymmetric C2 and the crystal structure of guest-absorbed 1•2 was solved in this space group. In the large asymmetric unit of the 1•2 structure, eight independent guest molecules were observed at sites A to H (Figure 2).…”
mentioning
confidence: 99%
“…A detailed structural analysis and mechanistic and theoretical study to elucidate this remarkable ring contraction are reported separately. 14 …”
mentioning
confidence: 99%